The making of the modern child : children's literature and childhood in the late eighteenth century - O'Malley, Andrew, 1968- (New York : Routledge, 2003)
Explores how the concept of childhood in the Victorian era was constructed through the ideological work performed by children's literature, as well as contemporary pedagogical and medical writing.
The coach and six : chapbook residue in late eighteenth-century children's literature -- Class relations in middle-class children's literature : interacting with and representing the poor and the rich -- The medical management of the late eighteenth-century child -- Towards the self-regulating subject : teaching discipline in pedagogical systems and children's books -- Molding the middle-class subject of the future : applied lessons and the construction of gender roles -- The trajectory of children's literature into the early nineteenth century : moving toward a middle-class form of fantasy.
Includes bibliographical references (pages 165-180) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Children's literature, English -- History and criticism; English literature -- 18th century -- History and criticism; Children -- Books and reading -- Great Britain -- History -- 18th century; Children -- Great Britain -- History -- 18th century; Littérature de jeunesse anglaise -- Histoire et critique; Littérature anglaise -- 18e siècle -- Histoire et critique; Enfants -- Livres et lecture -- Grande-Bretagne -- Histoire -- 18e siècle.; Enfance -- Grande-Bretagne -- Histoire -- 18e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Children; Children -- Books and reading; Children's literature, English; English literature; Great Britain; 1700-1799; Criticism, interpretation, etc; History